(untitled) (Jurnal Teknologi Industri Pertanian, 2016)
Sengon (Paraserianthes falcataria (L) Nielsen), is a fast-growing tree species that widely planted in Indonesia. However, some of the wood properties such as low-density, low-hardness, and low-strength limits its utilization. A study was conducted to evaluate the effect of thermal compregnation on the physical as well as mechanical properties of Sengon boards. The tangential board (36 cm x12 cm x3 cm) were impregnated by chitosan solution 0,5% under different temperature levels (100°C, 120°C, and 140°C), then thermally compressed to be 1,5 cm thickness under different temperature levels (150°C, 170°C, and 190°C). Moisture content, density, hardness, springback, Modulus of Elasticity, and Modulus of Rupture of the experimental boards were evaluated. Microscopic feature of the boards were also evaluated using Scanning Electron Microscope (SEM).The results showed that thermal compregnation positively affected the density, hardness, MOE as well as MOR of the boards. Density of compregnated boards had increased 80.70% compared with uncompregnated boards.In addition, hardness of compregnated boards (286,91 kg/cm²) were increased 54.61% compared with uncompregnated board (159,20 kg/cm²). Thermal compregnation was also increase MOE and MOR of Sengon boards as much as 53.20% and 52.77%, respectively. Meanwhile springback of compregnated boards were significant decrease by chitosan impregnation.The optimum temperature for impregnation as well as compression process of the boards were 100°C and 150°C respectively. Keywords: chitosan, compregnation, density, mechanical strength, sengon